Cardiac patterns for differentiation of neurogenic stunned myocardium in aneurysmal subarachnoid hemorrhage versus acute ischemic stroke. Issue 4 (7th March 2023) - Chang, Jason J.; Fazlalizadeh, Hooman; Dowlati, Ehsan; Triano, Matthew; Withington, Charles; Felbaum, Daniel R.; Mai, Jeffrey C.; Armonda, Rocco A.; Kumar, Preetham; Kenigsberg, Benjamin; Medvedofsky, Diego
Abstract: Aims: Neurogenic stunned myocardium (NSM) has heterogeneous presentations for acute ischemic stroke (AIS) and aneurysmal subarachnoid hemorrhage (SAH). We sought to better define NSM and differences between AIS and SAH by evaluating individual left ventricular (LV) functional patterns by speckle tracking echocardiography (STE). Methods: We evaluated consecutive patients with SAH and AIS. Via STE, LV longitudinal strain (LS) values of basal, mid, and apical segments were averaged and compared. Different multivariable logistic regression models were created by defining stroke subtype (SAH or AIS) and functional outcome as dependent variables. Results: One hundred thirty‐four patients with SAH and AIS were identified. Univariable analyses using the chi‐squared test and independent samples t ‐test identified demographic variables and global and regional LS segments with significant differences. In multivariable logistic regression analysis, when comparing AIS to SAH, AIS was associated with older age (OR 1.07, 95% CI 1.02–1.13, p = 0.01), poor clinical condition on admission (OR 7.74, 95% CI 2.33–25.71, p < 0.001), decreased likelihood of elevated admission serum troponin (OR .09, 95% CI .02–.35, p < 0.001), and worse LS basal segments (OR 1.18, 95% CI 1.02–1.37, p = 0.03). Conclusion: In patients with neurogenic stunned myocardium, significantly impaired LV contraction by LS basal segments was found in patients with AIS but not with SAH. Individual LV segments in our combined SAH and AIS population were also not associated with clinical outcomes. Our findings suggest that strain echocardiography may identify subtle forms of NSM and help differentiate the NSM pathophysiology in SAH and AIS.